2024
DOI: 10.21203/rs.3.rs-3830452/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superior Performance of Artificial Intelligence Models in English Compared to Arabic in Infectious Disease Queries

Malik Sallam,
Kholoud Al-Mahzoum,
Omaima Alshuaib
et al.

Abstract: Background Assessment of artificial intelligence (AI)-based models across languages is crucial to ensure equitable access and accuracy of information in multilingual contexts. This study aimed to compare AI model efficiency in English and Arabic for infectious disease queries. Methods The study employed the METRICS checklist for the design and reporting of AI-based studies in healthcare. The AI models tested included ChatGPT-3.5, ChatGPT-4, Bing, and Bard. The queries comprised 15 questions on HIV/AIDS, tube… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Similarly, Banimelhem and Amayreh reported suboptimal English to Arabic translation capabilities for ChatGPT [38]. Additionally, a recent study showed the superior performance of four generative AI models in English compared to Arabic in infectious disease queries [39], while an earlier study showed the inferior performance of ChatGPT in general health queries in Arabic dialects [35]. Additionally, the inferior performance of AI chatbots was reported in other non-English languages including Chinese [40], Polish [41], and Spanish [42].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Banimelhem and Amayreh reported suboptimal English to Arabic translation capabilities for ChatGPT [38]. Additionally, a recent study showed the superior performance of four generative AI models in English compared to Arabic in infectious disease queries [39], while an earlier study showed the inferior performance of ChatGPT in general health queries in Arabic dialects [35]. Additionally, the inferior performance of AI chatbots was reported in other non-English languages including Chinese [40], Polish [41], and Spanish [42].…”
Section: Discussionmentioning
confidence: 99%